Physical Activity and Recreation as Strategies to Impact Local Communities and Promote the Development of Soft Skills in Students: The Experience of University Extension with Students From Different Careers at the Interuniversity Campus of Alajuela, Costa - Miranda-Benavides, Yanixa (2021)
This article discloses situations students from different careers of the National University, Alajuela Interuniversity Campus, have experienced. As part of their learning process in the course “Actividades y Eventos Recreativos” (Activities and Recreational Events), they designed and practiced actions that promote physical and recreational activities in different communities in Alajuela, one of the seven provinces of Costa Rica. This exercise proves that it is possible to reinforce students’ abilities and impact local communities through learning and extension programs. For the systematization of this experience, the students and people in charge of organizations where the activities took place were asked to fill out a questionnaire to know their perception regarding the obtained results.